2007
DOI: 10.1093/ajcn/86.4.1016
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variation in glutathione and cysteine redox states in human plasma

Abstract: Cys/CySS and GSH/GSSG redox states in human plasma undergo diurnal variation with an increased magnitude of variation in Cys/CySS redox state in older persons. This variation could alter sensitivity to oxidative stress over a course of hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
147
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(155 citation statements)
references
References 33 publications
7
147
1
Order By: Relevance
“…These proteins may contribute to Cd-induced toxicity by concerning with GSH complexly, therefore, we protein levels and consider the contribution to the diurnal variation of Cd toxicity. There are many reports indicating the diurnal variation of GSH levels in plasma in addition to liver (Jaeschke and Wendel, 1985;Blanco et al, 2007;Xu et al, 2012). We estimated the hepatic levels of GSH in this report, therefore, we need further information about the GSH levels in plasma.…”
Section: Discussionmentioning
confidence: 97%
“…These proteins may contribute to Cd-induced toxicity by concerning with GSH complexly, therefore, we protein levels and consider the contribution to the diurnal variation of Cd toxicity. There are many reports indicating the diurnal variation of GSH levels in plasma in addition to liver (Jaeschke and Wendel, 1985;Blanco et al, 2007;Xu et al, 2012). We estimated the hepatic levels of GSH in this report, therefore, we need further information about the GSH levels in plasma.…”
Section: Discussionmentioning
confidence: 97%
“…However, the extent to which NAC affects tissue GSH in humans is difficult to assess. Recent data showing that GSH/GSSG and Cys/CySS redox states undergo a diurnal variation linked to dietary intake of sulfur amino acids (16) suggest careful timing and dosing may be needed because NAC absorption and clearance are rapid. Furthermore, homeostatic regulation of Cys and GSH declines with age, and this occurs at a younger age in men than in women (16).…”
Section: Oxidative Stress As a Disruption Of Redox Signaling And Controlmentioning
confidence: 99%
“…Recent data showing that GSH/GSSG and Cys/CySS redox states undergo a diurnal variation linked to dietary intake of sulfur amino acids (16) suggest careful timing and dosing may be needed because NAC absorption and clearance are rapid. Furthermore, homeostatic regulation of Cys and GSH declines with age, and this occurs at a younger age in men than in women (16). Thus dosing regimens may be critical in development of antioxidant strategies designed to protect or correct disruption of thiol redox systems by nonradical oxidants.…”
Section: Oxidative Stress As a Disruption Of Redox Signaling And Controlmentioning
confidence: 99%
“…Previous studies have shown characteristic changes in plasma thiol levels and steady-state redox potential with age, becoming highly significant between young (<30) and older (>60) adults, irrespective of other demographic factors [1,[19][20][21][22]. To evaluate clinical utility of the FTMS method, 5 young (mean age = 25.7 ± 3.3 y) and 5 older (mean age = 67.8 ± 6.3 y) adults were recruited to determine the ability of the LC-FTMS method to detect and quantify plasma thiol levels and steady-state redox potential changes with age.…”
Section: Evaluation Of Plasma Thiol/disulfide Oxidative Stress With Agementioning
confidence: 99%